Neonatal Outcome in Babies Born to Mothers with Meconium-Stained Amniotic Fluid - Kasi, Najia; Shaista Ambreen; Arshad Khushdil; Nidda Yaseen; Sidra Khalid; Nadeem, Warda Ali (Indus Journal of Bioscience Research, 2025)
Background: Meconium-stained amniotic fluid (MSAF) is a critical obstetric condition often associated with adverse neonatal and maternal outcomes. Despite the well-documented risks, the relationship between MSAF and complications such as Hypoxic-Ischemic Encephalopathy, Meconium Aspiration Syndrome, and other systemic neonatal issues remains an area of significant clinical interest. Objective: To evaluate the neonatal outcomes in babies born to mothers with meconium-stained amniotic fluid. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from July 2023 to January 2024 in the Department of Obstetrics and Gynecology, CMH Multan.  Methodology: A total of 207 neonates born to mothers with visible MSAF at or beyond 34 weeks of gestation were included. Preterm neonates, those with congenital malformations, twin pregnancies, or requiring surgical interventions, were excluded. Data collection covered demographic and clinical parameters, including gestational age, mode of delivery, birth weight, Apgar scores, and complications. Neonatal outcomes such as Meconium Aspiration Syndrome, Hypoxic-Ischemic Encephalopathy, Acute Renal Failure, and Necrotizing Enterocolitis were analyzed. Results: The mean gestational age at birth was 37.5 ± 2.21 weeks, and cesarean sections accounted for 71.5% of deliveries. Complications were prevalent, with Hypoxic-Ischemic Encephalopathy observed in 68.1% of neonates, Acute Renal Failure in 71%, and Meconium Aspiration Syndrome in 44.9%. The mortality rate was 21.7%. Conclusion: Meconium stained amniotic fluid is associated with a substantial burden of neonatal complications, emphasizing the necessity for vigilant monitoring, timely interventions.